Advances in understanding the mode of action of MBT fungicide used in wood protection - Singh, T.; Wakeling, R.; Kreber, B.; Jaspers, M.V.; Stewart, A. (New Zealand Plant Protection, 2002)
Interactions between methylene bisthiocyanate (MBT) and common wood degrading fungi of Pinus radiata were investigated The minimum inhibitory concentration (MIC) of MBT was determined in yeastmalt liquid medium and on radiata pine Higher treatment concentrations of MBT were required to control fungal growth on wood than in liquid culture irrespective of the test fungus used There were significant differences between the test fungi for MIC levels of MBT on diptreated wood with the highest degree of tolerance observed for Trichoderma viride (MIC le; 064 w/v) Further experiments suggested that vapour action and diffusibility both contributed to the fungitoxicity of MBT